Achieving inorganic growth through fintech investment (study case: pt. Bank tabungan negara (persero) tbk) - David Hutajulu, Hatorangan; Azhari Nasuation, Reza (The Indonesian Journal of Business Administration, 2018)
Abstract-In this thesis, the authors propose Bank ABC to build a partnership with Fintech through an investment scheme so that in the financial aspect, the bank can get more capital and in the business aspect, has the ability to integrate innovative solutions with the Fintech with the aim of seizing new markets, differentiating themselves in the future and ensure long-term sustainability. Chapter 1 describes the thesis framework that explains the background, the bank overview, the outline of the business issue, the objectives, scope and limitations of the study. Next in Chapter 2, the method will be used in this study is quantitative analysis. The technique used to collect data is by literature review and questionnaire. The authors developed several questionnaire items to capture Banks perceptions about the investment partnership with Fintech and several different questions about Fintech's self-assessment based on partner criteria that have been designed by authors. Chapter 3 will propose solutions for the investment model and how to get selected Fintech partners based on Fintech’s self-assessment result from previous questionnaire. After analyzing the data, the authors calculate the weighted score by using Kepner Tregoe method to get the best Fintech candidate as a partner. Finally in Chapter 4, this paper concludes by suggesting a specific CVC (Corporate Venture Capital) as a suitable model of investment unit for ABC in collaboration with Fintech startup and what criteria can be used to select Fintech candidates Keyword: collaboration, Fintech, partnership, investment